2013
DOI: 10.1093/jxb/ert094
|View full text |Cite
|
Sign up to set email alerts
|

BZR1 and BES1 participate in regulation of glucosinolate biosynthesis by brassinosteroids in Arabidopsis

Abstract: The effect of 24-epibrassinolide (EBR) on glucosinolate biosynthesis in Arabidopsis thaliana was investigated in the present study by using mutants and transgenic plants involved in brassinosteroid (BR) biosynthesis and signal transduction, as well as glucosinolate biosynthesis. The results showed that EBR significantly decreased the contents of major aliphatic glucosinolates including glucoiberin (S3), glucoraphanin (S4), and glucoerucin (T4), as well as the indolic glucosinolates glucobrassicin (IM) and neog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 39 publications
4
44
0
Order By: Relevance
“…A number of studies have been conducted with the aim of improving these properties. Chemical regulation was one of the most studied methods, especially with phytohormones, which have been reported to play important roles in the regulation of glucosinolate biosynthesis (Yuan et al, 2010a;Guo et al, 2013a;Kim et al, 2013;Schweizer et al, 2013;Frerigmann and Gigolashvili, 2014;Zang et al, 2015). Our previous research indicated that 5% (0.05 g/ml) glucose elevated glucosinolate in Chinese kale and pak choi sprouts (Wei et al, 2011) and the study by Huang et al (2014) showed a promoting effect of 100 μmol/L GA 3 on glucosinolate content in the siliques of oilseed rape.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have been conducted with the aim of improving these properties. Chemical regulation was one of the most studied methods, especially with phytohormones, which have been reported to play important roles in the regulation of glucosinolate biosynthesis (Yuan et al, 2010a;Guo et al, 2013a;Kim et al, 2013;Schweizer et al, 2013;Frerigmann and Gigolashvili, 2014;Zang et al, 2015). Our previous research indicated that 5% (0.05 g/ml) glucose elevated glucosinolate in Chinese kale and pak choi sprouts (Wei et al, 2011) and the study by Huang et al (2014) showed a promoting effect of 100 μmol/L GA 3 on glucosinolate content in the siliques of oilseed rape.…”
Section: Discussionmentioning
confidence: 99%
“…The glucosinolate content varies depending on genetic and environmental factors, and is modulated by external signals such as sugar (Miao et al, 2013) and phytohormones (Yuan et al, 2009;Sun et al, 2012;Wang et al, 2012;Guo et al, 2013a;2013b;Huseby et al, 2013;Kim et al, 2013;Zang et al, 2015). Glucose is not only the basal carbon and energy source but also a signaling molecule having regulatory effects throughout the life cycle of plant (Sheen, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It involves the integration of signals from sugars (Miao et al, 2013), brassinosteroids (Guo et al, 2013a), jasmonic acid (Guo et al, 2013b), salicylic acid (Mewis et al, 2005), ethylene, and auxin (Schweizer et al, 2013), in addition to a network of TFs (Gigolashvili et al, 2007;Malitsky et al, 2008;Sønderby et al, 2010). Our analysis has identified several TF as potential regulators of GS biosynthesis in the Arabidopsis funiculus.…”
Section: The Funiculus As a Center For Cellular Bioenergetics And Fatmentioning
confidence: 90%
“…GSs were extracted and analyzed as described previously (Guo et al, 2013). Leaf samples (200 mg) from the wild type (Col-0) or the transgenic bC1 expression line (bC1-1/At) were used.…”
Section: Gs Assaymentioning
confidence: 99%